DNA-linked inhibitor antibody assay (DIANA) as a new method for screening influenza neuraminidase inhibitors - Kožíšek, Milan; Navrátil, Václav; Rojíková, Kateřina; Pokorná, Jana; Berenguer Albiñana, Carlos; Pachl, Petr; Zemanová, Jitka; Machara, Aleš; Šácha, Pavel; Hudlický, Jason; Císařová, Ivana; Řezáčová, Pavlína; et al. (Biochemical journal (London. 1984), 2018)
Influenza neuraminidase is responsible for the escape of new viral particles from the infected cell surface. Several neuraminidase inhibitors are used clinically to treat patients or stockpiled for emergencies. However, the increasing development of viral resistance against approved inhibitors has underscored the need for the development of new antivirals effective against resistant influenza strains. A facile, sensitive, and inexpensive screening method would help achieve this goal. Recently, we described a multiwell plate-based DNA-linked inhibitor antibody assay (DIANA). This highly sensitive method can quantify femtomolar concentrations of enzymes. DIANA also has been applied to high-throughput enzyme inhibitor screening, allowing the evaluation of inhibition constants from a single inhibitor concentration. Here, we report the design, synthesis, and structural characterization of a tamiphosphor derivative linked to a reporter DNA oligonucleotide for the development of a DIANA-type assay to screen potential influenza neuraminidase inhibitors. The neuraminidase is first captured by an immobilized antibody, and the test compound competes for binding to the enzyme with the oligo-linked detection probe, which is then quantified by qPCR. We validated this novel assay by comparing it with the standard fluorometric assay and demonstrated its usefulness for sensitive neuraminidase detection as well as high-throughput screening of potential new neuraminidase inhibitors.
Keywords: Antiviral Agents; Oseltamivir; Humans; Phosphorous Acids; chřipka lidská; reprodukovatelnost výsledků; Drug Evaluation, Preclinical; Neuraminidase; virové proteiny; virus chřipky A; Influenza, Human; kyseliny fosforité; inhibitory enzymů; Influenza A virus; Viral Proteins; antivirové látky; DNA; preklinické hodnocení léčiv; lidé; Reproducibility of Results; neuraminidasa; oseltamivir; Enzyme Inhibitors